2005
DOI: 10.1111/j.1423-0410.2005.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Report of the First International Workshop on molecular blood group genotyping

Abstract: The use of molecular genetic technology for blood group typing is becoming routine procedure in many reference laboratories worldwide. A First International Workshop was organized on behalf of the International Society of Blood Transfusion (ISBT) and the International Council for Standardization in Haematology (ICSH). Thirty laboratories that provide a molecular diagnostic service participated in the workshop. Six samples were distributed: two represented DNA from transfusion-dependent patients for testing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 17 publications
1
35
0
6
Order By: Relevance
“…As most countries have only one or a few laboratories carrying out this work, an international EQA scheme is required. The International Society of Blood Transfusion (ISBT) organized international workshops in molecular blood group genotyping in (Daniels et al, 2005, 2007). In the most recent workshop (2008), two plasma samples from pregnant D-negative women, one with a D-positive and one with a D-negative fetus, were distributed to 17 laboratories (14 from Europe, 1 each from Australia, Brazil and China).…”
Section: Quality Assurancementioning
confidence: 99%
“…As most countries have only one or a few laboratories carrying out this work, an international EQA scheme is required. The International Society of Blood Transfusion (ISBT) organized international workshops in molecular blood group genotyping in (Daniels et al, 2005, 2007). In the most recent workshop (2008), two plasma samples from pregnant D-negative women, one with a D-positive and one with a D-negative fetus, were distributed to 17 laboratories (14 from Europe, 1 each from Australia, Brazil and China).…”
Section: Quality Assurancementioning
confidence: 99%
“…The following steps were taken into account: i) Manual isolation protocol of cf-DNA from 800 μl of maternal plasma using the commercial QIAamp DNA Blood Mini kit which was compared to automated isolation of cf-DNA from 400 μl of maternal plasma using the Biorobot EZ1 workstation and the commercial EZ1 Virus Mini Kit v2. This comparison showed that automated extraction improved the yields of cf-DNA, so we consider it as a reliable method of cff-DNA isolation from maternal plasma for non-invasive fetal RHD genotyping (data not published); ii) In order to assess the quality of our approaches, we have participated in the International Workshop on Molecular Blood Group Genotyping since 2004 [13,14,36,37], as well as in the evaluation of the International Reference Reagent for the detection of RHD and SRY DNA in plasma performed by The National Institute for Biological Standards and Control (NIBSC) from UK plasma [29]; iii) Similarly, we have followed the recommendations for routine screening of the ) for the human RhDpositive male genomic DNA standard, and median values and ranges of detected genomic equi valent (GE)/ml (GE = 6.6 pg human DNA) of cf-DNA and cff-DNA in maternal plasma for the tested genes…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies are based on a variety of quantitative realtime polymerase chain reaction (qPCR) protocols [10][11][12]. In order to resolve numerous technical issues regarding the RHD genotyping from maternal plasma, several studies and workshops have been performed, such as the International Workshop on Molecular Blood Group Genotyping (testing since 2004) and workshops under the auspices of the Special Advances in Fetal and Neonatal Evaluation (SAFE) Network of Excellence [13][14][15]. However, so far, only Denmark and the Netherlands have introduced fetal RHD typing in RhD-negative pregnant women as a routine screening program [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, the International Society of Blood Transfusion (ISBT) organized a workshop on molecular blood group genotyping. Thirty laboratories participated and the workshop culminated in a feedback meeting and was the precursor of an international quality assurance scheme [18]. Subsequently there have been ISBT workshops every second year, the year of the ISBT International Congress, with a feedback meeting at that congress [19][20][21].…”
Section: Workhops and External Quality Assurancementioning
confidence: 99%